A concepção estrutural como expressão plástica: um olhar tectônico sobre arquitetura em madeira - Galvão, Fernando de Medeiros (2009)
This work regards to the structural conception as a formal element of design in wood architecture. On this approach, the group of projects studied is formed by some realized works of two important Brazilian architects: Severiano Porto and Marcos Acayaba. The time interval comprises the period from 1971 to 1997, which correspond respectively to the years of the creation of first and the last of the analyzed constructions. The research perspective concerns to the relationship between the parts, the whole and the building techniques adopted in each project. Moreover, the analysis focuses on the structure as the link among the different projectual ideas. Thus, the research method firstly includes a survey of specific bibliographies and documents which refer to the structural conception in wood architecture. Secondly,the buildings are analyzed according to the methods of architectural composition discussed through this work.